Nghiên cứu cơ chế phản ứng giữa gốc propargyl với phân tử cacbon monoxit (CO) bằng phương pháp hoá học lượng tử - Tiến, Phạm Văn; Thùy, Phan Thị; Hoàn, Phạm Thọ; Minh Huệ, Nguyễn Thị; Cường, Ngô Tuấn (Vietnam Journal of Chemistry, 2017)
The reaction mechanism of the Propargyl radical and carbon monoxide has been studied by the Density Functional Theory (DFT) using the B3LYP functional in conjunction with the 6-311++G(3df,2p) basis sets. We used the natural population atomic (NPA) charges analysis and MO energy of reactants to predict initial direction of the reaction. The potential energy surface (PES) for the C3H3 and CO system was also established. Our calculated results indicate that products of this reaction can be (HCCCC + H2O), (HCCCH + HCO), (H2CCC + HCO), (r-HCCCCOH), (HCCO+C2H2), and (CCCCHO + H2). However, the formation of (HCCO+C2H2) is the most favorable. This study is a contribution to the understanding of the reaction mechanisms of the propargyl radical with many small radicals and molecules in the atmosphere and combustion chemistry. Keywords. Reaction mechanism, propargyl radical, oxygen, density functional theory.